The Prospects of Conventional and Alternative Energy Production in the Countries of the Balkan Peninsula (in the Context of Developing Economic Indicators) - Guliev, Igbal Ð.; Geladze, Shota A.; Sokolova, Elizaveta S.; Egorova, Larisa I. (International Journal of Energy Economics and Policy, 2019)
The article is devoted to revealing the main problems and prospects of the energy industry on the Balkan Peninsula. Due to the lack of natural resources and the low ecology standards of current energy production, reforms in the sphere are needed. There are two main approaches to these reforms that are pinpointed by the authors in the article: the development of shale resources, that is cheaper and the development of alternative energy, that is much more eco-friendly. In order to specify the path, that a Balkan country is likely to choose, the countries are divided into groups by geographical conditions and the synthesis of geographical, ecological and energy data results in a complex analysis of the energy production prospects in the region. The authors develop a special index, demonstrating the difficulty of energy production development in the region. Based on this index, the strategies to overcome the problems in the industry are offered. Special attention is payed to grouping the measures for the first and second group of countries, in which they were divided by geographical conditions. The key findings include the mentioned index, the strategies for the countries and the development of financial model of cooperation with international organizations without undermining the fragile peace in the region. Keywords: the Balkan Peninsula, alternative energy, index, shale resources, strategy, energy independency JEL Classifications: O13, Q4 DOI: https://doi.org/10.32479/ijeep.8290